Stopping power and energy loss for protons in Be plasmas - He, Bin; Meng, Xu-Jun; Wang, Jian-Guo (21st International Symposium on Heavy Ion Inertial Fusion. Autonomous Organization of Education “Nazarbayev University”, 2016)
Stopping power (SP) for ions in plasmas is a basic and old problem, which data is important for heavy ion driven inertial fusion and heavy ion transport in hot matters. So far there are some relevant experiments and many theoretical researches...
Keywords: power; energy; protons; Research Subject Categories::NATURAL SCIENCES::Physics::Elementary particle physics